2017
DOI: 10.1021/acs.inorgchem.7b02034
|View full text |Cite
|
Sign up to set email alerts
|

A Cationic Coordination Polymer and Its Orange II Anion-Exchanged Products: Isolation, Structural Characterization, Photocurrent Responses, and Dielectric Properties

Abstract: Solvothermal reactions of AgNO with N,N-bis(5-fluoropyridin-3-yl)succinamide (bfps) in MeCN afforded the one-dimensional cationic coordination polymer {[Ag(bfps)]NO} (1). Upon treatment of 1 with the anionic azo dye orange II (NaOII) in aqueous solution, the NO anions of 1 could be gradually exchanged by the OII anions via an anion-exchange process. The resulting OII anion-exchanged products {[Ag(bfps)](NO)(OII)} (2) and {[Ag(bfps)](NO)(OII)} (3) were formed by different molar ratios of 1 and the newly formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…It can also be seen from the Table that the ability of dye adsorption of MOG2 is better than that of MOG1. There have been many literature reports on dye adsorption every year. The MOGs have advantages on adsorption efficiency and diversity as well as material costs.…”
Section: Resultsmentioning
confidence: 99%
“…It can also be seen from the Table that the ability of dye adsorption of MOG2 is better than that of MOG1. There have been many literature reports on dye adsorption every year. The MOGs have advantages on adsorption efficiency and diversity as well as material costs.…”
Section: Resultsmentioning
confidence: 99%
“…Recently we have found that some one-dimensional (1D) CPs showed excellent adsorption capacities toward organic dyes, and the resultant CP-dye composites displayed better electronic performances. For example, the 1D CP {[Ag­( bfps )]­NO 3 } n ( bfps = N 1 , N 4 -bis­(5-fluoropyridin-3-yl)­succinamide) (Scheme ) could absorb Orange II (OII) with a capacity of 662 mg·g –1 ) . The as-prepared CP-OII composite demonstrated enhanced photocurrent responses and improved dielectric properties relative to those of the parent CP.…”
Section: Introductionmentioning
confidence: 96%
“…For example, the 1D CP {[Ag-(bfps)]NO 3 } n (bfps = N 1 ,N 4 -bis(5-fluoropyridin-3-yl)succinamide) (Scheme 1) could absorb Orange II (OII) with a capacity of 662 mg•g −1 ). 48 The as-prepared CP-OII composite demonstrated enhanced photocurrent responses and improved dielectric properties relative to those of the parent CP. The preliminary results encouraged us to expand the 1D CPs into higher dimensional structures which might have diversiform topologies and better thermal and water stabilities.…”
Section: ■ Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[15,16] Many CPs absorb organic dyes and the resulting composites exhibit improved photoelectric responses. [17,18] For example, a one dimensional (1D) CP of Zn(II), 1,2,3-BTA (1,2,3-benzenetricarboxylate) and N,N'-di(3-pyridyl)succinamide showed superior Congo Red (CR) sorption up to 1129 mg/g, and the resulting composite exhibited a remarkably enhanced photocurrent response. [17] Scientists usually aim to maximize the uptake of dye and thereby to maximize photocurrent, but without specifically designing for this parameter.…”
mentioning
confidence: 99%